THE INFLUENCE OF THE ELECTRONIC KANBAN IN THE STOCK CONTROL OF MACHINING TOOLS - RIBEIRO, MÁRCIO SOUZA; BONATO, SAMUEL VINICIUS; PEREIRA JUNIOR, ERROL FERNANDO ZEPKA; LOPES, CYNTHIA MIKAELA CHEMELLO FAVIARO; LEITE, FELIPE KOPP (Revista e-TECH: Tecnologias para Competitividade Industrial - ISSN - 1983-1838, 2025)
The research highlights the advantages of using a simple tool like kanban, often considered outdated, in achieving organizational objectives. It also emphasizes the importance of investing in infrastructure and fostering relationships with suppliers. The study identifies the reasons behind a company’s adoption of a new inventory management methodology and the development of the e-kanban system. The research explores how electronic kanban controls tools used in machining materials. Using a qualitative approach and a case study method, it focuses on a leading auto parts company. Data collection involved field observation and document analysis, with data tabulation and graphical layouts used to analyze inventory management models. The study demonstrates that kanban, despite being labeled obsolete, can reduce costs and waste in production processes, enabling organizational objectives. It also highlights the importance of strong supplier relationships for maximizing the tool’s potential. A limitation of the research was the inability to conduct interviews with company managers. Additionally, the observation technique posed challenges, such as potential researcher bias and the risk of missing key phenomena. The findings suggest that high investment in new methodologies is not always necessary to achieve objectives. The e-kanban system effectively reduces production costs and improves inventory accuracy. The research illustrates how a Brazilian company maintains leadership in a complex sector by leveraging this simple tool. Despite its origins in a different context, kanban continues to offer tangible benefits to organizations today.